Building Sustainable Public Sector Capacity in a Challenging Context - World Bank Group (World Bank, Washington, DC, 2017)
In a conflict-affected and newly independent country like South Sudan, rebuilding public sector capacity is an important aspect of state building, both in the short and in the medium to long term. If capacity strengthening is not pursued or is ineffective, government functionality remains patchy and dependency on technical assistants (TA) remains high. Capacity strengthening has been considered amorphous and a difficult topic in academic literature. This paper looks at the experience of efforts to strengthen capacity in South Sudan over the decade from 2005 to 2016. The context has proved challenging for capacity-building efforts. On the one hand, some improvements have been seen and some skilled civil servants are in place. On the other hand, wider progress has been difficult and punctuated by crises and setbacks. Renewed conflicts from December 2013 to August 2015, and again since July 2016, have disrupted progress and planning for development support. The report’s recommendations are based on the assumption that minimum stability will eventually return for capacity strengthening to restart; but it cannot be predicted when this will be the case.